5 1/4 - 2 2/3
first you find the LCM, so u can make both fractions have a like denominator. I'm thinking the LCM is 12, so:
(5 3/12) - (2 8/12)
= 63/12 - 32/12
=31/12
= 2 and 7/12
5 1/4 - 2 2/3 = 2 7/12
Answer:
I've already answered :) Please give Brainliest ;)
Step-by-step explanation:
Since it is an equality that means the left side of the equation (x/8) has to be equal to the right side of the equation (28/32). One way you can solve for x is to isolate it. Since it’s an equality like we said you have to do to the left side the same that you would do to the right side to isolate x. So if I multiply by 8 on the left I need to also multiply by 8 on the right. So 8* (x/8) becomes just x since 8x/8 becomes 8/8 * x which is 1 *x. On the right side we do 8 *(28/32) which becomes 28 * 8/32 which becomes 7. So x = 7.
Answer: Lucy pays $ 492.58 back altogether.
Step-by-step explanation:
Formula : Interest = Principal x Rate x Time
Given: Principal = $425 , rate = 5.3% = 0.053 , time = 3 years
Interest = 425 x 0.053 x 3 ≈ $ 67.58
Total amount need to pay back = Principal + Interest
= $ (425+67.58)
= $ 492.58
Hence, Lucy pays $ 492.58 back altogether.
Answer:
I will use "complete-the-square" approach if thats ok
first 0.5(x - 2)² - 2
second -2(x - 4)² + 8